2012
DOI: 10.3389/fendo.2012.00095
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms and Clinical Consequences of Vascular Calcification

Abstract: Vascular calcification has severe clinical consequences and is considered an accurate predictor of future adverse cardiovascular events, including myocardial infarction and stroke. Previously vascular calcification was thought to be a passive process which involved the deposition of calcium and phosphate in arteries and cardiac valves. However, recent studies have shown that vascular calcification is a highly regulated, cell-mediated process similar to bone formation. In this article, we outline the current un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
109
1
3

Year Published

2013
2013
2019
2019

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 99 publications
(114 citation statements)
references
References 196 publications
(246 reference statements)
1
109
1
3
Order By: Relevance
“…[36][37][38] In contrast, increased levels of PP i are known to inhibit vascular calcification. 39 The ENPP1 K173Q mutation identified in this study has previously been shown to affect intracellular ENPP1 activity and serum ENPP1 enzyme levels. 40,41 In both our discovery and validation studies, we found that the ENPP1 K variant was associated with a significantly decreased stroke risk, which suggests that decreased ENPP1 activity may protect against stroke via PP i levels.…”
Section: Discussionmentioning
confidence: 63%
“…[36][37][38] In contrast, increased levels of PP i are known to inhibit vascular calcification. 39 The ENPP1 K173Q mutation identified in this study has previously been shown to affect intracellular ENPP1 activity and serum ENPP1 enzyme levels. 40,41 In both our discovery and validation studies, we found that the ENPP1 K variant was associated with a significantly decreased stroke risk, which suggests that decreased ENPP1 activity may protect against stroke via PP i levels.…”
Section: Discussionmentioning
confidence: 63%
“…Consequently, no effective therapies are available. Increasing body of recent evidence has challenged the traditional consideration of vascular calcification as a passive aging-related process and points to specific mechanisms of its regulation depending on diseaserelated environmental cues [32,33]. A role of circulating calcifying cells in this process is emerging [34].…”
Section: Discussionmentioning
confidence: 99%
“…It shares some outward similarities with bone mineralisation and is associated with a phenotypic transdifferentiation of vascular smooth muscle cells (VSMCs) towards a more osteoblast-like phenotype [80].…”
Section: Pyrophosphate and Vascular Calcificationmentioning
confidence: 99%